Airline competition and market frequency: A comparison of the s-curve and schedule delay models. (August 2015) - Hansen, Mark; Liu, Yi
Highlights: We compare s-curve and schedule delay models in airline frequency competition. We compare competitive equilibria for the two models with empirical evidence. The schedule delay model more accurately predicts observed market outcomes. 1-stage and 2-stage equilibria are the same for both model structures. For given traffic, frequency is the same under competition and social optimality. Abstract: We compare two common ways of incorporating service frequency into models of airline competition. One is based on the so called s-curve, in which, all else equal, market shares are determined by frequency shares. The other is based on schedule delay—the time difference between when travelers wish to travel and when flights are available. We develop competition models that differ only with regard to which of the above approaches is used to capture the effect of frequency. The demand side of both models is an approximation of a nested logit model which yields endogenous travel demand by including not traveling in the choice set. We find symmetric competitive equilibrium for both models analytically, and compare their predictions concerning market frequency with empirical evidence. In contrast to the s-curve model, the schedule delay model depicts a more plausible relationship between market share and frequency share and accurately predicts observed patterns of supply side behavior. Moreover, the predictions from both models are largely the same if we employ numerical versions of the model that capture real-world aspects of competition. We also find that, for either model, the relationship between airline frequency and market traffic is the same whether frequency is determined by competitive equilibrium, social optimality, or social optimality with a break-even constraint.